A narrative review of vaccine-induced thrombotic thrombocytopenia in organ donation and transplantation: Current evidence and implications - Vivek B Kute; Sanshriti Chauhan; Narayan Prasad; Hari Shankar Meshram (Indian Journal of Transplantation, 2023)
Vaccine-induced thrombotic thrombocytopenia (VITT) has been recently linked with coronavirus disease (COVID-19) vaccines. It becomes crucial for the transplant communities to have a rigorous approach for accepting VITT donors, as the reports of such transplantation have been associated with thrombotic complications, graft loss, and deaths. The magnitude of facing a VITT donor in transplantation practices is unknown and also the management protocol. However, as per the limited data, it is better to avoid such transplants, and in the case of emergency transplants, the risk-benefit ratio should be weighed. All transplantation from VITT donors should be appropriately counseled before procurement. The organs should undergo deliberate examination for functionality by clinical, laboratory, and radiological parameters. In doubtful cases, a preimplantation biopsy is mandated to rule out any thrombosis. VITT donors are suggested to be treated with newer oral anti-coagulation and intravenous immunoglobulin. Platelet transfusion is best avoided in a VITT donor. There is no established protocol for any modification in surgical procedure, anesthesia, or immunosuppressive medicines in the recipients. The recipients should undergo extensive clinical and laboratory monitoring for any possible complications. No prophylactic therapy is recommended at present but candidates with a history of any COVID-19 vaccine within 30 days, should be avoided. In summary, the evidence for diagnosis and management of VITT donors is based only on a few reports, but with current knowledge, it is advisable to take a multidisciplinary approach to assess all benefits and risks before accepting or discarding organs.